Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Melalui Motivasi Kerja Pada Badan Pendapatan Daerah (BAPENDA) Kota Tasikmalaya - Abdillah, Luthfi Muhammad Nauval; Arga Sutrisna; Ai Kusmiati (CV. ITTC INDONESIA, 2024)
This study aims to determine how the work environment and motivation can affect the performance of employees of the Tasikmalaya City Regional Revenue Agency. The subjects in this study were employees of the Tasikmalaya City Regional Revenue Agency (BAPENDA). The sampling technique used was saturated sampling where the entire population became the research sample, which was 72 employees. This research method uses a quantitative method. The analysis tool uses path analysis (flow analysis) with the help of SPSS 29 software. Based on the results of the study, it can be concluded that the work environment does not affect work motivation, the work environment has a negative and significant effect on employee performance, work motivation has no effect on employee performance, and the work motivation variable cannot mediate between the work environment variable and employee performance at the Tasikmalaya City Regional Revenue Agency (BAPENDA).